2022
DOI: 10.1111/jopy.12742
|View full text |Cite
|
Sign up to set email alerts
|

Development of intraindividual value structures in middle childhood: A multicultural and longitudinal investigation

Abstract: IntroductionWe examined changes in value inter-relations during middle-childhood. In line with the Personal Values Theory (Schwartz, 1992), we expected a value system, with individuals similarly valuing related motivations, and setting priorities between conflicting motivations (Döring et al., 2016;Schwartz, 1992). We hypothesized this system to develop dynamically during middle-childhood, as children deepen their understanding of their own values (Shachnai & Daniel, 2020). Method Using unfolding analysis (Bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…There are previous indications that suggest that values develop during middle childhood. As early as 5–6 years of age, children can report their value priorities (Abramson et al., 2018; Döring et al., 2016), but their value priorities still change (Daniel et al., 2020) as do value inter‐relations (Daniel et al., 2022; Lee et al., 2017). Importantly, previous initial results also suggest that at the same period of development, values increasingly are described as motivations rather than behaviors (Shachnai & Daniel, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are previous indications that suggest that values develop during middle childhood. As early as 5–6 years of age, children can report their value priorities (Abramson et al., 2018; Döring et al., 2016), but their value priorities still change (Daniel et al., 2020) as do value inter‐relations (Daniel et al., 2022; Lee et al., 2017). Importantly, previous initial results also suggest that at the same period of development, values increasingly are described as motivations rather than behaviors (Shachnai & Daniel, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a crosssectional study, the relations between values of ten-to 12-year-olds were more structurally coherent than those of 6to 9-year-old children, suggesting increasing differentiation among the ten values (Abramson et al, 2018). Daniel et al (2022) 2020) investigated a sample of children ages 5-13 years. They asked children to elaborate on the meaning, within their life, of their own values in order to draw conclusions, not about value priorities, but about the underlying understanding of values, and specifically whether they conceptualized.…”
Section: The Values Model and Children's Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted, research on adults and adolescents has shown repeatedly (Sagiv & Schwartz, 2021; Schwartz, 1992) systematic conflicts and compatibilities in the motivations underlying different values. Thus, values typically show coherence , with individuals’ values reflecting the motivational compatibilities and incompatibilities among values (Daniel, Döring, & Cieciuch, 2023). In addition, values are abstract, referring to ideas rather than specific objects, contexts, or behaviors.…”
Section: Five Value Maturation Criteriamentioning
confidence: 99%